Financial Condition, Growth, Audit Quality and Going Concern Opinion: Study on Manufacturing Companies Listed on Indonesia Stock Exchange - ., Mukhtaruddin; Pratama, Handri; Meutia, Inten (Journal of Accounting, Business and Finance Research, 2018)
Going concern audit opinion is accepted by the company represents the presence of conditions within the auditor doubts of the company’s going concern. Going concern audit opinion can be used for the users of the financial statements in making investment decisions in a company. This study examines the effect of the company's financial condition, company’s growth, and audit quality on acceptance of going concern audit opinion. This research uses 252 sample of manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2010-2012. The hypotheses in this research investigated using logistic regression. The hypothesis testing showed that company’s financial condition influence the acceptance of the going concern audit opinion, while company’s growth and audit quality do not influence the acceptance of going concern audit opinion. So the limitation of this research is this research only on manufacturing company the writer hope in the next research could do a research in a different sector for showing a consistency research result.